Debates About Neuroethics : Perspectives on Its Development, Focus, and Future - Racine, Eric; Aspler, John (Advances in Neuroethics, 2017)
This is the first book entirely dedicated to exploring issues associated with the nature of neuroethics. It reflects on some of the underlying assumptions in neuroethics, and the implications of those assumptions with respect to training and education programs, research activities, policy engagement, public discourse, teaching, ethics consultation and mentoring, to name but a few areas of interest. Internationally respected and emerging leaders in the area have taken up the pen to express and debate their views about the development, focus and future of neuroethics. They share their analyses and make recommendations regarding how neuroscience could more effectively explore and tackle its philosophical, ethical, and societal implications.